Toward a Geography of Rural Education in Canada - Corbett, Michael (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
The field of rural education has not been significantly developed in Canada and the marginal status of the rural itself has contributed to this peripheral status. The emergence of geography and spatial thinking generally in social theory and in educational thought represents an opportunity to re-evaluate the importance of space and place in educational theory and policy discourse. Rather than a space formal education leaves behind, or as the location of impoverishment, isolation, and deficit, I argue that rural communities occupy an important place on the Canadian educational landscape. Given the economic, political, and cultural challenges they face, I suggest rural schools may produce higher quality educational outcomes than are generally attributed to them.